Cyborg as a cyborgizated human being: the philosophical thought experiment in film 'Robocop' (2014) - Rayhert, Konstantin (Skhid, 2017)
The study analyzes a philosophical thought experiment conducted in film 'Robocop' (2014). The film models the situation within which a human being is transformed into a cyborg, human-robotic hybrid, and explores different treatment of the hybrid. To be a cyborg in film 'Robocop' (2014) is to experience of three kinds of treatments to itself. First kind of treatments shown by Raymond Sellars' position is not to perceive a cyborgizated human being as a human and to treat of him as of a robot. Second kind of treatments shown by Alex Murphy' position to perceive a cyborgizated human being as a human and to treat of him as a human being. Third kind of treatment shown by Doctor Dennett Norton's position is to perceive a cyborgizated human being as a human and to treat of him as a human being but at the same time to think that at the physical level there is no difference between a human being and a robot. Potentially the third kind erases out differences between a human being and a machine held an artificial intelligence what leads to paradox: the technologies which extend human abilities can replace the very human being. The third kind can wipe off the differences between a human being and a machine held an artificial intelligence at physical (neural networks), juridical (machines held artificial intelligence may have rights, freedoms and duties), and ethical (Is it allowed to eliminate machines held artificial intelligence?) levels.